Can participative coach behaviour be perceived as controlling? The role of athletes` expectations - Van Meervelt, K.; Van Puyenbroeck, S.; Vande Broek, G. (European Journal of Sport Science, 2023)
Coach-rated participative behaviour has already been related to beneficial outcomes in athletes. Yet, research also indicates that allowing participation is not straightforward as it can sometimes be perceived as controlling or can even result in maladaptive outcomes. Building on implicit leadership theory, this study investigated the role of the alignment between coach-rated participation and athletes` expectations for participation in developing perceptions of domineering coach behaviour in athletes, a specific type of controlling coach behaviour. A secondary goal was to explore this relation in higher and lower level teams separately. Athletes` expectations for participative coach behaviour, coach-rated participative behaviour and athletes` perceptions of domineering coach behaviour were measured in 61 team sport coaches and 654 athletes competing in football, volleyball, basketball, and handball competitions. Using polynomial regression with response surface analysis and controlling for athletes` sport experience, overall, results showed that a discrepancy between coach-rated participation and athletes` expectations for participation was related with increased perceptions of domineering coach behaviour in athletes with more than 5 years of experience. However, in lower level teams, high amounts of participation seem optimal as only less coach-rated participation than expected predicted increased perceptions of domineering coach behaviour in athletes with more than 15 years of experience. This in contrast with higher level teams where, independent of athletes` experience, both more and less coach-rated participation than expected were related with increased perceptions of domineering coach behaviour in athletes. Current findings stress the need for a situation specific approach when offering participation to optimize its effectiveness.